Pengaruh Budaya Organisasi terhadap Kinerja Karyawan - Agustina, Dini Rahma; Andriani, Andriani; Mahfudhotin, Mahfudhotin (Reinforce: Journal of Sharia Management, 2025)
Organizational culture is a system of values and norms that have taken effect, followed and agreed upon by each member as a guide in behaving and solving problems in their organization. Organizational culture is closely related to employee performance because the organizational culture in a company is able to foster the work spirit of the people in it. This study aims to determine the organizational culture and employee performance according to employees in the production department of PT Sukses Mitra Sejahtera, Krandang Village, Kras District, Kediri Regency. The method used is a quantitative method. Variables X and Y are in the "sufficient" category. The level of correlation between organizational culture and employee performance is moderate, this is in accordance with the r value of 0.561. Simple linear regression test, the direction of the influence of variable X on variable Y is positive (25.203) and every 1% increase in value of variable X, the value of variable Y will increase by 0.524. The results of the t-test show that there is a significant influence of organizational culture variables on employee performance, this is based on the t-count of 10.050 > t table 1.651 with a significance of 0.000 < 0.05. Ho is rejected and Ha is accepted. The results of the determination coefficient test value R2 0.315 means that variable X is able to explain variable Y by 31.5%, the remaining 68.5% is explained by other variables not included in this study.